Strategi Kampanye @Kpop4planet Dalam Membangun Kepedulian Generasi Z Akan Krisis Iklim Global - Puspita Sari, Ni Putu Yuni; Purnawan, Ni Luh Ramaswati; Suryawati, I Gusti Agung Alit (E-Jurnal Medium; Vol 5 No 1 (2024): Jurnal Ilmu Komunikasi Vol 5 No 1 Tahun 2024, 2024)
The research objective of this study was to examine the strategy employed by the @kpop4planet campaign in raising awareness among Generation Z about the global climate crisis. The study utilised a qualitative methodology with a descriptive approach. Data collection involved online interviews and observations. The Nowak and Warneryd Digital Campaign Models were used to analyse the campaign strategy implemented by @kpop4planet through social media content dissemination, focusing on cultivating awareness among Generation Z regarding the global climate crisis. The results of the study indicate that the virtual community @kpop4planet effectively executed its communication strategy through the No K-Pop On A Dead Planet campaign. The campaign utilised written content, photos, and videos on social media platforms to not only raise awareness but also to encourage Generation Z to develop an affinity for the environment similar to their admiration for their favourite K-Pop idols.